2018
DOI: 10.1371/journal.ppat.1007266
|View full text |Cite
|
Sign up to set email alerts
|

NLRC3 negatively regulates CD4+ T cells and impacts protective immunity during Mycobacterium tuberculosis infection

Abstract: NLRC3, a member of the NLR family, has been reported as a negative regulator of inflammatory signaling pathways in innate immune cells. However, the direct role of NLRC3 in modulation of CD4+ T-cell responses in infectious diseases has not been studied. In the present study, we showed that NLRC3 plays an intrinsic role by suppressing the CD4+ T cell phenotype in lung and spleen, including differentiation, activation, and proliferation. NLRC3 deficiency in CD4+ T cells enhanced the protective immune response ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 42 publications
3
36
1
Order By: Relevance
“…NLRC3 has been shown to participate in a lot of pathological processes. For example, Hu et al reported that NLRC3 negatively regulates CD4+ T cells and impacts protective immunity during Mycobacterium tuberculosis infection . Guo et al demonstrated that NLRC3 promotes host resistance against Pseudomonas aeruginosa ‐induced keratitis by promoting the degradation of interleukin 1 receptor associated kinase 1 (IRAK1) .…”
Section: Discussionmentioning
confidence: 99%
“…NLRC3 has been shown to participate in a lot of pathological processes. For example, Hu et al reported that NLRC3 negatively regulates CD4+ T cells and impacts protective immunity during Mycobacterium tuberculosis infection . Guo et al demonstrated that NLRC3 promotes host resistance against Pseudomonas aeruginosa ‐induced keratitis by promoting the degradation of interleukin 1 receptor associated kinase 1 (IRAK1) .…”
Section: Discussionmentioning
confidence: 99%
“…Although NLRC3 has been demonstrated as a negative regulator in macrophages and T cells (Schneider et al, 2012;Zhang et al, 2014;Hu et al, 2018), the specific role of NRLC3 in DCs still remains poorly understood. In the presence of DC-maturing stimuli, DCs uptake antigens and mature to become the most potent antigenpresenting cells accompanied by upregulation of MHC II and costimulatory molecules (Guermonprez et al, 2002).…”
Section: Nlrc3 Deficiency Promotes Antigen-presenting Function Of Dcsmentioning
confidence: 99%
“…It has been reported that NLRC3 is expressed by many types of cells, including T cells (Hu et al, 2018;Uchimura et al, 2018) that influence activity of DCs via their interactions. Thus, it still remains unclear about the direct contribution of NLRC3 regulates DCs during EAE progression.…”
Section: Nlrc3 Expression In DC Restricts Eae Progressionmentioning
confidence: 99%
See 2 more Smart Citations